The Psychological Motive in the Duality of Disease and Medicine in the Abbasid Era - Mahmoud, Shaima Iyad; Ibrahim, Muhammad Khalil; Abd, Abd Mahmoud (Journal of Tikrit University for Humanities, 2024)
Poetic creativity is not devoid of incentives and motives that make the poets creative in describing their reality, or what they intend to discuss, especially when it relates to the psychological or physical pains they endure. It may also reflect what they seek to glorify in their poetry, stemming from their personal and realistic experiences. The primary psychological incentive for this creativity is the disease caused by psychological distress. This ailment intensifies and subsides in accordance with the severity of psychological pains or their absence in the individual. It is harmonized with their psychological feelings, which paint the picture of their suffering in poetry, attempting to obtain relief through their complaints, descriptions, or lamentations. This desire and aspiration are driven by the longing for something they have been deprived of in an influential environment.